ANALYSIS OF RELATED FACTORS WITH IMMUNIZATION OF MEASLES IN BABY AGE 9-12 MONTHS IN PUSKESMAS SUKAKARYA SABANG CITY - Andika, Fauziah (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2017)
Measles is still one of the causes of death in children, despite the availability of effective and safe vaccines. Increased measles immunization programs have a major impact on reducing death rates from measles. Measles is the leading cause of death in children worldwide throughout the year. In the world is estimated every year there are 30 million people who suffer from measles. The purpose of this study was to analyze the factors associated with measles immunization in infants aged 9-12 months in Sukakarya Health Center Sabang City. This research is quantitative using analytic with cross sectional design. The population in this study were all mothers who had 9-12 month old infants amounted to 284 people with total sample of 39 0rang. The data was collected from August 02 until August 05, 2017 assisted by enumerator with data processing using chi square test and 95% CI. The result of this research is the correlation of knowledge with measles immunization (p value = 0.127), attitude relation with measles immunization (p value = 0.001), health officer support relationship with measles immunization (p value = 0.001). The conclusion of this study is that there is no relationship between knowledge with measles immunization, there is a correlation between attitude and support of health officer with measles immunization. It is expected that health workers provide re-counseling on the importance of measles immunization and provide support to mothers to be motivated to immunize against measles on time.Keywords: Measles Immunization, Knowledge, attitude and support of health officer